Development Of LKPD Using Scientific Approach To Improve High School Student’s Understanding Of Concepts And Scientific Thinking Abilities On Excretion System - Setyaningsih, Tri; Saptono, Sigit (Universitas Negeri Semarang, 2025)
The purpose of this study is to analyze validity, readability, and effectiveness of the student worksheet using scientific approach to improve understanding concepts and scientific thinking on excretory system material. The research was conducted at SMA N 2 Kebumen with a sample of 70 students of class XI-A and XI-B. The type of this study is Research & Development. This development was limited to the large scale test. The data collection technique used in this study is the questionnaire method and the pretest and posttest test methods. The result showed that the validity by matrial expert obtained high validity criteria with an average score of 92,5% and an average score by material expert of 88,75% obtained a high valid criterion. The readability test of student’s worksheet was tested on limited students with 9 students of class XI-C Senior High School 2 Kebumen and 1 biology teacher. The result of the response of student obtained 87,03% with very good criteria. The result of teacher response obtained 97,72% with very good criteria. Then the results of the N-Gain data pretest and posttest are included in the high category. Classical completion is 90%. Based on these results, it can be concluded that the student worksheet using scientific approach on excretory system materials is very valid and readability very well and effective in improving understanding concepts and scientific thinking.